Overcoming language barriers: lessons learnt from migrant children - Ke Yu; Balungile Shandu (Perspectives in Education, 2018)
In this paper, we identify reasons for the high school achievement of some migrant children, in spite of the language barriers faced by themselves and their parents. We explore the literature to determine the factors used to overcome such barriers, particularly those beyond social economic status (SES) and other largely inherited factors that remain a common focus of migration and school effectiveness literature. We identify the need to pay greater attention to non-conventional factors, such as aspirations, expectations and creativities. We also examine school effectiveness literature in South Africa, arguably a typical case of a developing country, and note that much of the literature centres on analysis and lamentation of physical and human resource constraints, instead of experimenting on non-conventional factors.